IMPLEMENTATION OF GOTO TRADEMARK PROTECTION BASED ON THE PRINCIPLE OF “SUBSTANTIAL SIMILARITY” - Richie Fernando; Gunawan Djajaputra (Bengkoelen Justice : Jurnal Ilmu Hukum, 2025)
Trademark protection is a crucial aspect of intellectual property law, aimed at safeguarding trademark owners and preventing consumer confusion. This study analyzes the implementation of the "substantial similarity" principle in a trademark dispute case involving the registered trademark owner "GOTO" against similar trademark variations, such as "goto" and "Goto Financial." Using a normative approach, this research evaluates trademark infringement based on visual, phonetic, and conceptual similarities, which may cause confusion and potential loss to the actual trademark owner. The findings indicate that the principle of "substantial similarity" plays a vital role in maintaining the exclusive rights of registered trademark owners while providing legal certainty and fairness in resolving trademark disputes. These findings reinforce the importance of strong trademark protection regulations to prevent conflicts and safeguard brand reputation in an increasingly competitive market. Keywords: Trademark Protection, Substantial Similarity, Exclusive Rights, Trademark Dispute